Vocabulary Development and Kinship Level of Javanese Dialect: Dialect Geography Studies - Wibowo, Ridha Mashudi (Allure Journal, 2024)
Â This study aims to explore the extent of vocabulary and kinship changes in Javanese dialects in Yogyakarta Special Region between 2019 and 2023. Data tapping was conducted at a number of observation points, namely in the villages of Kebonrejo (Kulonprogo), Pakem Binangun (Sleman), Segoroyoso (Bantul), Planjan (Gunungkidul), and Ngringin (Gunungkidul). The data were obtained using the basic Morris Swadesh vocabulary, the universal vocabulary of the world's languages. By looking at the data obtained from the same observation points in 2019 and 2023, it is possible to compare the vocabulary developed in Javanese dialects. From the data comparison, it is also possible to compare the level of kinship between dialects to see if there is a shift in their status from different speech, subdialect, dialect, or language. The data were obtained by tapping method with recording and note-taking techniques, then analyzed by comparison, introspection, and dialectometry methods, and presented by formal methods in the form of tables and figures and informal methods in the form of ordinary narratives. The results show changes in vocabulary and kinship levels caused by internal elements, namely vocabulary development, heterogloss, and dialectometry, and external language, namely factors of dialect supporting communities, dialect area development, and the Covid-19 pandemic.